BETWEEN HINDU INDONESIA AND THE HARE KRISHNA MOVEMENT: A MINORITY PROBLEM - Lemuel Christandi, Yohanes Babtista (International Journal of Humanity Studies (IJHS), 2025)
The conflict between Hindu Indonesia or Indonesian Hinduism and Hare Krishna movements in Indonesia is between two religious groups that are not solely about theological differences but also political. Under Parisada Hindu Dharma Indonesia (PHDI), Indonesian Hinduism gained recognition from the state after making several adjustments and changes. The entanglement of Indonesian Hinduism and Balinese cultures was knitted during the struggle for recognition. It led to a fixed, specific identity and character of Indonesian Hinduism. The case of a series of rejections toward the Hare Krishna movement sparked in the Hindu members who escalated with Desa Adat involvement and reached a deadlock with the statements of PHDI. This paper investigates the issues between Indonesian Hinduism and the Hare Krishna Movements through a literature review. It aims to answer questions about how the conflict between Indonesian Hinduism and the Hare Krishna movements presents the complexities of the socio-cultural politics of governing religion in Indonesia. Finally, it argues that the conflict between Indonesian Hinduism and the Hare Krishna movement reflects the effects of governing religious differences in Indonesia.